Transferable aspherical atom model refinement of protein and DNA structures against ultrahigh‐resolution X‐ray data. Issue 6 (1st June 2016) - Malinska, Maura; Dauter, Zbigniew
Abstract : This paper presents the advantages of using the transferable aspherical atom model of macromolecular structure refinement against ultrahigh‐resolution X‐ray data over the classic independent‐atom model approach in terms of final crystallographic statistics, the description of atomic displacement parameters and the quality of electron‐density maps. Abstract : In contrast to the independent‐atom model (IAM), in which all atoms are assumed to be spherical and neutral, the transferable aspherical atom model (TAAM) takes into account the deformed valence charge density resulting from chemical bond formation and the presence of lone electron pairs. Both models can be used to refine small and large molecules, e.g. proteins and nucleic acids, against ultrahigh‐resolution X‐ray diffraction data. The University at Buffalo theoretical databank of aspherical pseudo‐atoms has been used in the refinement of an oligopeptide, of Z‐DNA hexamer and dodecamer duplexes, and of bovine trypsin. The application of the TAAM to these data improves the quality of the electron‐density maps and the visibility of H atoms. It also lowers the conventional R factors and improves the atomic displacement parameters and the results of the Hirshfeld rigid‐bond test. An additional advantage is that the transferred charge density allows the estimation of Coulombic interaction energy and electrostatic potential.